Analisis Kohesi Gramatikal dan Leksikal pada Teks Eksposisi Siswa Kelas 10 Sekolah Menengah Atas - Yustina Dwinuryati; Andayani Andayani; Retno Winarni (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2018)
This study aims to describe the use of grammatical and lexical cohesion markers, the variation of the grammatical and lexical cohesion markers use, and the misuse of cohesion markers on the exposition of the students. The method used in this research is descriptive qualitative method. Data sources came from a collection of students expository text, with purposive sampling as data analysis technique. The results of this study indicates that: (1) the most used grammatical cohesion marker by class X IPS 2 students is the reference form with the highest appearance of 42 data, while the lexical cohesion marker most used is form repetition with the highest appearance of 13 data; (2) the use of the grammatical and lexical cohesion marker in writing the exposition has been shown to be varied, although the use is still uneven; (3) the most common misuse of grammatical cohesion marker in the student exposition is the use of the conjunction with the percentage of 73.08%.